Implications of Transforming Household Livelihoods through Villagization in Conserving Forest Resources in Southwest Ethiopia: A Case Study of Mengeshi District, Gambela Region. Issue 1 (5th July 2019) - Aba, Abera; Urgessa, Kaba; Kebebew, Zerihun
ABSTRACT: Villagization brings scattered households together into a defined area with the aim of transforming living conditions through providing social and economic services. As the forest in Mengeshi district, southwest Ethiopia, has been destroyed through shifting cultivation, the study aims at assessing the effect of villagization on conserving forest resources. Three sites were selected, these being at Fejeji, Baya and Kumi. A total of 119 households were selected for interviews. Information was collected through structured and semi-structured questionnaires. Six farms and 18 plots were assessed for woody plants. The results show that the most important changes which positively contribute towards forest resources were perceived after villagization. A total of 34 woody species representing 13 families were identified in the abandoned farms. Economically important species including Cordia africana Lam., Pouteria altissima (A.Chev.) Baehni and Diospyros abyssinica (Hiern) F. White that need conservation due to overutilization were recorded across the three sites. The Simpson's diversity index was 0.94 at Fejeji, 0.93 at Baya and 0.88 at Kumi. Villagization has brought about changes in the sources of livelihoods of the households. The forest-based livelihoods have shifted to farming-based livelihoods and the main sources of forest products have shifted from forest to homestead. A paired t- test showed a significant change in the forest product sources implying less pressure on natural forest resources. In general villagization has positive effects towards conserving forest resources in the area.